Lysyl oxidase suppresses the inflammatory response in anterior cruciate ligament fibroblasts and promotes tissue regeneration by targeting myotrophin via the nuclear factor‐kappa B pathway. (21st June 2020) - Wang, Chunli; Sha, Yongqiang; Wang, Sixiang; Chi, Qingjia; Sung, K.L. Paul; Xu, Kang; Yang, Li
Abstract: Anterior cruciate ligament (ACL) regeneration is severely affected by the injury‐induced overexpression of matrix metalloproteinases (MMPs) and downregulation of lysyl oxidase (LOX). Previous studies have focused on how the expression of MMPs and downregulation of LOX are physiologically balanced at injured sites for regenerating the ACL tissue, but the role of LOX in regulating cellular functions has not been investigated yet. Herein, we conducted an in vitro cellular experiment and unexpectedly found that exogenous LOX inhibited the expression of MMPs and inflammatory factors and recovered the cell growth; thus, LOX strongly inhibited the tumor necrosis factor‐alpha (TNF‐α)‐induced inflammatory responses. In an in vivo animal model, LOX supplementation suppressed the expression of TNF‐α in injured ACLs and promoted the recovery of the damaged tissues. RNA‐sequencing‐identified differentially expressed genes (DEGs) were highly enriched in the nuclear factor‐kappa B (NF‐κB), chemokine, cytokine‐cytokine receptor interaction, Toll‐like receptor, and TNF signaling pathways. Immunofluorescence tracing was employed to localise the exogenous LOX in the cell nucleus; the exogenous LOX indirectly suggests that it has other biological roles apart from the cross‐linking of the extracellular matrix. Protein–protein interaction network analysis revealed the anti‐inflammatory effect of LOX was alleviated by silencing the myotrophin (MTPN) expression, suggesting that LOX might interact with MTPN and regulate inflammation. Finally, this study suggests that LOX can inhibit the inflammatory response of ACL fibroblasts (ACLfs) and promote the recovery of the damaged ACL tissue through the MTPN‐mediated NF‐κB signaling pathway.